"Don't buy" or "do not buy"? How negation style in online reviews influences consumer product evaluations. Issue 3 (3rd July 2021) - Kim, Soyoung; Moore, Sarah G.; Murray, Kyle
ABSTRACT: We investigate how different negation styles – that is, contracted (e.g., "isn't") versus full negations (e.g., "is not") – in electronic word-of-mouth (eWOM) influence consumers' evaluations of and willingness to pay for target products. We find that consumers evaluate products more positively when reviews contain contracted negations, as compared to full negations. This occurs because consumers perceive a reviewer who uses contracted negations as warmer and thus more competent than one who uses full negations; these positive perceptions increase consumers' product evaluations. This research identifies a novel social pathway underlying consumers' information processing in reviews and highlights the social aspects of eWOM.